INFORMATION AND COMMUNICATION TECHNOLOGIES IN SCIENCE AND EDUCATION OF MODERN SOCIETY - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article investigates the impact of ICT on the development of modern science and education.